THE ANALYSIS OF STRATEGIC BUSINESS ABOUT RANGERS FRIED CHICKEN IN TAIPEI, TAIWAN: Universitas Budi Luhur Jakarta - ., Nabilah; Khalid, Zulvia (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This study uses SWOT analysis and Porter's five forces model to analyze the strategic environment of 德州美墨炸雞 Rangers Fried Chicken (RFC) in Taipei, Taiwan. The study aims to evaluate the internal and external factors of RFC and provide insights into RFC's competitiveness in the Taiwanese fast food market. The results not only highlight RFC's strengths such as strong brand, product quality and service system, but also significant challenges such as intense competition and changing consumer preferences. The study provides strategic recommendations to enhance RFC's competitive advantage and ensure long-term sustainability.